Hydrolysis of Dipeptides Catalyzed by a Zirconium(IV)‐Substituted Lindqvist Type Polyoxometalate. Issue 26 (29th July 2013) - Ly, Hong Giang T.; Absillis, Gregory; Bajpe, Sneha R.; Martens, Johan A.; Parac‐Vogt, Tatjana N.
Abstract: The hydrolysis of a series of unactivated dipeptides in the presence of a zirconium(IV)‐substituted Lindqvist type polyoxometalate, (Me4 N)2 [W5 O18 Zr(H2 O)3 ] (designated as ZrW5 ), was studied by kinetic experiments and NMR spectroscopy. Among the dipeptides examined, those with the X–Ser amino acid sequence were most effectively hydrolyzed. The kinetics of the hydrolysis of histidylserine (His–Ser) was studied in detail; a rate constant of 95.3 (± 0.1) × 10 –7 s –1 (pD 7.4 and 60 °C) in the presence of an equimolar amount of ZrW5 was calculated. The binding of His–Ser to ZrW5 was examined by UV/Vis, 1 H, 13 C, and 183 W NMR spectroscopy, and the data indicate that at physiological pD His–Ser chelates the Zr IV through its imidazole nitrogen, amine nitrogen, and amide carbonyl oxygen. In the presence of ZrW5, the pD profile of k obs is bell‐shaped, with a maximum reaction rate at pD 7.5. At high pD values an inactive complex is formed as a result of the deprotonation of the amide nitrogen, resulting in inhibition of His–Ser hydrolysis. The effects of pH, temperature, inhibitors, and ionic strength on the hydrolysis rate constant were also investigated, and a full account of the mechanism of this novel reaction is given. Abstract : The hydrolysis of dipeptides in the presence of a zirconium(IV)‐substituted Lindqvist type polyoxometalate was investigated. Of the dipeptides studied, His–Ser was most effectively hydrolyzed, with a first‐order rate constant of 9.53 × 10 –6 s –1 at pD 7.4 and 60 °C. The binding of His–Ser to the Zr complex and the effect of pH, temperature, inhibitors, and ionic strength on the rate constant were examined.